Analysis of 40 conventional and emerging disinfection by-products in fresh-cut produce wash water by modified EPA methods. (1st August 2018) - Lee, Wan-Ning; Huang, Ching-Hua; Zhu, Guangxuan
Highlights: Three methods to analyze 23, 9 and 8 DBPs, respectively, in produce wash water. Six emerging DBPs, not in the original EPA methods, are added. Method modifications improved extraction efficiency and lowered matrix interference. The optimized methods can be easily adopted by most labs due to common instrument. One of the first studies to analyze such a wide range of DBPs in produce wash water. Abstract: Chlorine sanitizers used in washing fresh and fresh-cut produce can lead to generation of disinfection by-products (DBPs) that are harmful to human health. Monitoring of DBPs is necessary to protect food safety but comprehensive analytical methods have been lacking. This study has optimized three U.S. Environmental Protection Agency methods for drinking water DBPs to improve their performance for produce wash water. The method development encompasses 40 conventional and emerging DBPs. Good recoveries (60–130%) were achieved for most DBPs in deionized water and in lettuce, strawberry and cabbage wash water. The method detection limits are in the range of 0.06–0.58 μg/L for most DBPs and 10–24 ng/L for nitrosamines in produce wash water. Preliminary results revealed the formation of many DBPs when produce is washed with chlorine. The optimized analytical methods by this study effectively reduce matrix interference and can serve as useful tools for future research on food DBPs.